Correlation Between Fagerstrom Score and Brinkman Index With Spirometry Results in Lung Cancer Patients at Haji Adam Malik General Hospital and Prof. Dr. Chairuddin Panusunan Lubis Hospital University of North Sumatera Medan - Agung Haganta Pinem; Setia Putra Tarigan; Amira P. Tarigan; Taufik Ashar (Jurnal Impresi Indonesia, 2025)
Lung cancer is one of the leading causes of cancer-related deaths globally. Cigarette smoking remains the primary risk factor. The Fagerstrom Test for Nicotine Dependence (FTND) and the Brinkman Index are used to assess nicotine addiction and smoking intensity, respectively. These indices are associated with pulmonary function, typically assessed through spirometry. Objective: To determine the relationship between Fagerstrom scores and Brinkman Index with spirometry results in lung cancer patients. Methods: This quantitative observational study applied a cross-sectional design involving 68 smoking lung cancer patients at RSUP Haji Adam Malik and RS Prof. CPL Universitas Sumatera Utara. Data were collected via FTND and Brinkman Index questionnaires and spirometry testing. Data were analyzed using the Kruskal-Wallis test with a significance level of p<0.05. Results: Most patients exhibited moderate nicotine dependence (44.1%) and moderate smoking history per Brinkman Index (52.9%). Spirometry results indicated a high prevalence of obstructive and restrictive impairments. There was a significant correlation between FTND/Brinkman Index and lung function (p<0.001). Conclusion: Both Fagerstrom scores and Brinkman Index show a strong relationship with spirometry outcomes, indicating impaired pulmonary function among lung cancer patients.